2023
DOI: 10.1057/s41599-023-01532-1
|View full text |Cite
|
Sign up to set email alerts
|

Social trust, social capital, and subjective well-being of rural residents: micro-empirical evidence based on the Chinese General Social Survey (CGSS)

Abstract: Despite a recent line of research highlighting trust as an important determinant of residents’ happiness in Western countries, empirical evidence regarding the strength of these linkages in the developing world needs to be more comprehensive and conclusive. This paper contributes to this literature by performing a deeper examination into the trust-based explanation of happiness and, particularly, exploring the mediating role of social capital in rural China, where rapid economic growth coexists with gradual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Item 2 is a reverse score question. The total score of these two questions represents the level of social trust of the respondents [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Item 2 is a reverse score question. The total score of these two questions represents the level of social trust of the respondents [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Positive dimensions focus on the question “In general, do you think that most people can be trusted?”. Negative dimensions focus on the view that “Others will find ways to take advantage of you if you are not careful” [ 24 , 25 ]. For the first question, if an individual’s score exceeds the median, it indicates a certain level of social trust; if it is below the median, it indicates a lack of social trust.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the valid data, coverage, and other information in various public databases in the existing literature, this paper finally determines that the data released by the large-scale social survey project "Chinese General Social Survey (CGSS)" hosted by the China Survey and Data Center of Renmin University of China will be used as the basic data. [18,19] CGSS is China's first national, comprehensive, and continuous large-scale social survey project, covering data from various aspects of the economy and society. [20] This paper selects CGSS-2017 data for research, and after preliminary screening, the valid sample size is 1092 valid samples.…”
Section: Data Sourcementioning
confidence: 99%
“…Trust expresses personal beliefs about social relationships and is necessary for creating such relationships and developing a sense of control and mastery of one's life (Mirowsky & Ross, 2017). The trust-SWB association is well documented in the empirical literature across countries and different population groups (e.g., Awaworyi Churchill & Mishra, 2017;Elgar et al, 2011;Gao & Zhao, 2022;Laurence, 2019;Xu et al, 2023), including adolescents (Tuominen & Haanpää, 2022). While, to my knowledge, studies that explored the trust-GLS link among young adults have not been conducted, a large-scale European study found that interpersonal trust is a positive and significant determinant of young adults' mental wellbeing (measures by the World Health Organization-5; Giovinazzo et al, 2022), and studies in the Israeli context have pointed to the protective effect of trust against psychological distress (Achdut, 2023) and loneliness (Achdut & Refaeli, 2020) among young adults.…”
Section: Ethnic Inequality In Life Satisfactionmentioning
confidence: 99%